96.8k views
2 votes
Simplify this radical. √x^13

User KooiInc
by
7.1k points

2 Answers

5 votes
x^(13/2) = x^(12/2)×sqrt(x)

x^6×sqrt(x) final answer

User Sam Woods
by
6.0k points
6 votes

Answer:


\sqrt{x^(13)} = x^(6) * √(x).

Explanation:

Given :
\sqrt{x^(13) }.

To find : Simplify this radical.

Solution : We have given
\sqrt{x^(13) }.

By the exponent same base rule :
x^(a) * x^(b) = x^(a +b).

Then we can write 13 as 12 + 1


x^(12) * x^(1) = x^(12+1).


x^(12) * x^(1) = x^(13).


\sqrt{x^(13)} = \sqrt{x^(12)* x^(1) }.

By the radical rule :
\sqrt{x^(a)* x^(b) } = \sqrt{x^(a)} * \sqrt{x^(b)}.

Then ,


\sqrt{x^(13)} = \sqrt{x^(12)} * √(x).


\sqrt{x^(13)} = x^{(12)/(2)} * √(x).


\sqrt{x^(13)} = x^(6) * √(x).

Therefore,
\sqrt{x^(13)} = x^(6) * √(x).

User Maccullt
by
5.7k points